Media Puzzle untuk Mengenal Bentuk Geometri - Ratna Pangastuti (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2019)
Learning media are all things that can be used to channel learning materials so that they can stimulate the attention, interests, thoughts and feelings of students (students) in learning activities to achieve certain learning goals. Learning media is a tool or other material that provides a complete form of information and can support the teaching and learning process. Learning in the introduction of geometric shapes in early childhood really requires appropriate learning strategies and media, so to maximize the child's ability to introduce geometric shapes can use puzzle media. Compiling geometric shapes puzzles can improve cognitive for children. Cognitive skills (cognitive skills) associated with the ability to learn and solve problems in children. Moreover, it can improve social skills for children. By using the content analysis method and the study documentation, this research tries to describe the puzzle media to introduce geometric shapes to early childhood